2022
DOI: 10.18502/jri.v23i1.8447
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Crocus sativus (Saffron) Petal Hydro-alcoholic Extract on Ovarian Follicle, Inflammatory Markers, and Antioxidant Enzymes in Mice Model of Polycystic Ovary Syndrome

Abstract: Background: Saffron petals have traditionally been used to treat a variety of diseases, such as gynecological diseases, primary dysmenorrhea, and premenstrual syndrome. Polycystic ovary syndrome (PCOS) is a kind of gynecological disease that causes infertility, menopausal and urogenital disorders and saffron petals seem to be an efficient treatment for such disorders. Methods: NMRI mice (total=60, each group n=12) were divided into control, PCOS, and the treatment groups. PCOS and treatment groups were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, SPA showed antioxidation, which was reflected in the increased levels of GPX, SOD, CAT, GST, and GSH enzymes in the plasma of PCOS mice after SPA treatment. Subsequently, these results ensured that the number of follicles and corpus luteum increased, and the number of cystic follicles decreased in PCOS mice (Moshfegh et al, 2022).…”
Section: Saffron Petal Anthocyaninsmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, SPA showed antioxidation, which was reflected in the increased levels of GPX, SOD, CAT, GST, and GSH enzymes in the plasma of PCOS mice after SPA treatment. Subsequently, these results ensured that the number of follicles and corpus luteum increased, and the number of cystic follicles decreased in PCOS mice (Moshfegh et al, 2022).…”
Section: Saffron Petal Anthocyaninsmentioning
confidence: 73%
“…Moshfegh et al utilized saffron petal anthocyanins (SPA) to treat testosterone-induced PCOS mice and disclosed that SPA could improve the hormone disorder, which was evidenced by the recovery of serum levels of LH, FSH, and steroid hormones (estrogen, progesterone, and testosterone) in mice (Moshfegh et al, 2022). In addition, SPA reduced the levels of the inflammatory cytokines TNF-α, IL-6, IL-1β, IL-18, and C-reactive protein (CRP), indicating that SPA demonstrated an anti-inflammatory effect by reducing the mRNA levels of inflammatory genes and restoring NF-κB and inhibitor of NF-κB (IκB) (key mediators of inflammatory genes), resulting in improvement of the inflammatory response of PCOS mice (Moshfegh et al, 2022). In addition, SPA showed antioxidation, which was reflected in the increased levels of GPX, SOD, CAT, GST, and GSH enzymes in the plasma of PCOS mice after SPA treatment.…”
Section: Saffron Petal Anthocyaninsmentioning
confidence: 99%
“…Previous studies have reported elevated levels of TNF-α and IL-6 in PCOS [36,50]. Several studies have shown signi cant reductions in the levels of these factors after treatment with compounds such as Gallic Acid [51], hawthorn leaf avonoids [52], Quercetin [53], resveratrol for TNF-α [32], saffron [54], and Ageratum conyzoides [36].…”
Section: Discussionmentioning
confidence: 99%
“…Besides studies conducted on the effect of C. sativus or its phytochemical compounds on modulating reproductive hormones and folliculogenesis (Mokhtari et al, 2010; Sadoughi, 2017; Vafa & Emadi, 2020), several studies have described the anti‐inflammatory property and anti‐oxidative capacity of this herb as a notable mechanism for the regulation and improvement of ovarian function and PCO (Hu et al, 2018; Moshfegh et al, 2022a; Sadoughi, 2017). In this regard, it has been confirmed that C. sativus is not only influenced by its modulatory effects on sex hormones, pituitary–gonadal axis, gonadotropin, and steroid receptors but also by regulating inflammatory‐related factors, and antioxidant enzymes (Table 2) (Chen et al, 2019; Moshfegh et al, 2022a; Moshfegh et al, 2022b; Zohrabi et al, 2018).…”
Section: Description Of Studiesmentioning
confidence: 96%